PENGARUH SIKAP PROFESIONAL, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA GURU DI SMA MUHAMMADIYAH 1 PONOROGO - Nayni Nayni; Adi Santoso; Eka Destriyanto Pristi Ayuningtyas (LP2M Universitas Bina Bangsa, 2023)
The purpose of this study is to find out whether there is an influence of professional attitudes (x 1) on teacher performance (y), the influence of work motivation (x 2) on teacher work performance (y), the influence of work discipline (X3) on teacher performance and to find out how much influence professional attitudes (x 1), work motivation needs (x 2) and work discipline (x 3 ) collectively affect teacher performance (y). The method used in this study is an observation method, with a quantitative approach of correlation and regression. The total sample of 45 people was taken from the teaching staff at Muhammadiyah 1Ponorogo High School. The data processing method uses multiple regression analysis. The results showed that the professional attitude variable i (x 1) there was a significant influence on teacher performance (y) as evidenced by the efficiency of the professional attitude variable i (x 1) with a calculated t test value of 3.225 > ttable 2.019, while the work motivation variable(x2 ) with a calculated t test value of 3.924 whose value is greater than t table 2.019, as for the work discipline variable (x 3) with a t hitun g test valueof 3.583 >2.019. Based on the f test, it shows that the probability value < 0.05, it can be said that there is a significant influence together between the free variables and the bound variables. This means that there is a positive influence between professional attitudes (x 1), work motivation (x 2), work discipline (x3) on teacher performance (y). The conclusion of the study based on the calculations above shows that there is a significant influence between professional attitude, work motivation and work discipline on teacher performance. Based on the results of the analysis, it can be concluded that together professional attitudes, work motivation and work discipline have a significant positive influence on the performance of teachers of SMA Muhammadiyah 1 Ponorogo